2014
DOI: 10.1371/journal.pone.0109908
|View full text |Cite
|
Sign up to set email alerts
|

Nothing Special in the Specialist? Draft Genome Sequence of Cryomyces antarcticus, the Most Extremophilic Fungus from Antarctica

Abstract: The draft genome of the Antarctic endemic fungus Cryomyces antarcticus is presented. This rock inhabiting, microcolonial fungus is extremely stress tolerant and it is a model organism for exobiology and studies on stress resistance in Eukaryots. Since this fungus is a specialist in the most extreme environment of the Earth, the analysis of its genome is of important value for the understanding of fungal genome evolution and stress adaptation. A comparison with Neurospora crassa as well as with other microcolon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…The analysis suggested that the genome of C. antarcticus is very similar in size, content and composition to the other black fungi considered. These results imply that either all these diverse environments impose similar ecological challenges for black fungi (for instance, low water activity or high irradiation), that their adaptations are useful in a wide range of conditions, or that their peculiarities might be mediated by uncharacterized mechanisms (Sterflinger et al, ). However, since their polyextremophilic properties emerge due to accumulation of chemical compounds and control of universal traits such as membrane fluidity, phenotypic variation should be easy without extensive genomic innovation.…”
Section: Black Fungimentioning
confidence: 98%
See 1 more Smart Citation
“…The analysis suggested that the genome of C. antarcticus is very similar in size, content and composition to the other black fungi considered. These results imply that either all these diverse environments impose similar ecological challenges for black fungi (for instance, low water activity or high irradiation), that their adaptations are useful in a wide range of conditions, or that their peculiarities might be mediated by uncharacterized mechanisms (Sterflinger et al, ). However, since their polyextremophilic properties emerge due to accumulation of chemical compounds and control of universal traits such as membrane fluidity, phenotypic variation should be easy without extensive genomic innovation.…”
Section: Black Fungimentioning
confidence: 98%
“…Whole‐genome duplication might be an important evolutionary step allowing adaptation to highly specialized extreme niches, although to date Hortaea remains the only described example. One of the first comparative studies of black fungi involved the sequencing of the psychrophylic Cryomyces antarcticus (Dothideomycetes incertae sedis ) (Sterflinger et al, ). They compared C. antarcticus with several species of black fungi isolated from diverse environments.…”
Section: Black Fungimentioning
confidence: 99%
“…The assembly completeness was also analyzed with Benchmarking Universal Single Copy Orthologs (BUSCO 3.0.1; Waterhouse et al 2017). In addition, 238 whole-genome assemblies of other Dothideomycetes were downloaded from NCBI Gen-Bank and the JGI Genome portal (Additional file 1: Table S1; Galagan et al 2005;Fedorova et al 2008;Sharpton et al 2009;Ellwood et al 2010;Desjardins et al 2011;Goodwin et al 2011;Rouxel et al 2011;Stukenbrock et al 2011;Chan et al 2012;Hu et al 2012;Joardar et al 2012;Ng et al 2012;Ohm et al 2012;Spatafora et al 2012;Blanco-Ulate et al 2013;Condon et al 2013;Lenassi et al 2013;Yew et al 2013;Aragona et al 2014;Bihon et al 2014;Chan et al 2014;Cooke et al 2014;Gao et al 2014;Gostinčar et al, 2014;Han et al 2014;Soliai et al 2014;Sterflinger et al 2014;van der Nest et al 2014;Yang et al 2014;Franco et al 2015;Grandaubert et al 2015;Kuan et al 2015;Morales-Cruz et al 2015;Orner et al 2015;Shaw et al 2015;Shiller et al 2015;…”
Section: Bioinformaticsmentioning
confidence: 99%
“…Signi cant ndings from studies in these organisms include the stimulation of growth of some fungi by low dose IR [20][21][22]; the possibility that melanin in the cell walls of certain fungi can protect against IR through shielding, free-radical scavenging, or a physiological mechanism [21,23]; the high IR resistance of organisms such as Ustilago maydis [24][25][26][27], Cryptococcus neoformans [19,23,28,29], Cryomyces antarcticus [30], and Exophiala dermatitidis [31]; and the discovery of novel IR-resistanceassociated proteins through transcriptomics and targeted mutagenesis [19,28,31]. A portion of the radioresistance of fungi can be explained by their genome size, which is approximately two orders of magnitude smaller than mammals, and therefore sustains less damage per unit dose of IR, but within fungi there is also considerable variation in resistance that is not explained by genome size or composition (for instance, see [12,[31][32][33]).…”
mentioning
confidence: 99%